Purification, biochemical characterization and localization at single cell resolution of Matrix Gla Protein (MGP) and Bone Gla Protein (BGP) in the teleost fish Argyrosomus regius - Simes, D (2016)
Tese de dout. em Química, Faculdade de Ciências do Mar e do Ambiente, Univ. do Algarve, 2002